Focus on the Performances of the Most Advanced Italian Thermoelectric Power Plants - Romano, Luigi; Ruberti, Marcello (International Journal of Energy Economics and Policy, 2019)
The key indicators, in the Annex IV of Regulation (EC) 1221/2009 (“EMAS III”), should permit an assessment of the environmental impact of an organization, through the quantification of resources and the evaluation of significant environmental aspects. The aim of this research is to carry out a brief survey on the suitable use and reporting of the performance indicators in the EMAS Environmental Statements of a very representative sample of Italian CCGT (Combined Cycle Gas Turbine) power plants and then on the state and evolution of few core energy and environmental indicators in order to investigate their benchmarking performances. Our findings are that the total consumption of fossil fuels and the overall emissions have greatly decreased in relation to the less operating time of the CCGT power stations, but, in relation to the electricity produced, the consumption of natural gas and the emissions of greenhouse gases have drastically increased. Keywords: CCGT power stations, EMAS Environmental Statement, performances. JEL Classifications: L940, Q310, Q41 DOI: https://doi.org/10.32479/ijeep.7906